The Dark Artifices: Lord of Shadows - Book 2 Book 2 - Clare, Cassandra (New York : Margaret K. McElderry Books, 2017)
Emma is torn between her passion for Julian and her need to protect him from the consequences of a forbidden romantic partnership, a situation challenged by her relationship with Mark and his efforts to regain his Shadowhunter capabilities.
"A shadowhunters novel."
Keywords: Supernatural -- Juvenile fiction; Demonology -- Juvenile fiction; Magic -- Juvenile fiction; Los Angeles (Calif.) -- Juvenile fiction; Paranormal -- Juvenile fiction; Fantasy -- Juvenile fiction